Meigs syndrome: literature review of a case report - Acuña Pinzón, Camilo Levi; Ugarte, Diego Hinojosa; Herevia, Aldo Edyair Jimenez; Guerrero, Miguel Angel (International Journal of Research in Medical Sciences, 2020)
Ovarian cancer is the presence of one or multiple tumors, which appears in one or both ovaries. These tumors are usually classified as epithelial and non-epithelial. Sex cord-stromal tumors are a group of benign and malignant neoplasms that develop from the sexual cord. Many are functional and therefore have hormonal secretions. Meigs syndrome is defined by the presence of pleural effusion and ascites in association with an ovarian tumor. We present a case of a 55 years old patient who was admitted due to a pelvic tumor, exudative pleural effusion that was difficult to manage, and ascites. A benign ovarian stromal tumor associated with elevated Ca 125 was diagnosed. After the management of the effusions, a 20x20x10 cm ovarian tumor resection was performed by laparotomy, and a transoperative report of a thecoma/fibroma type stromal tumor was received. Meigs syndrome occurs in 1% of ovarian tumors, being very rare before the third decade of life, the pathogenesis of ascites and pleural effusion could be related to the imbalance of hydrostatic forces between arterial flow and lymphovenous drainage culminating in a stromal transudate. Treatment of this syndrome should be focused on tumor debulking surgery and symptomatic treatments such as chest tubes and pleurodesis.